PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBANTUAN KOMPUTER DENGAN SOFTWARE CABRI 3D TERHADAP KEMAMPUAN GEOMETRI POKOK BAHASAN SUDUT DALAM RUANG DIMENSI TIGA SISWA KELAS X SMA NEGERI 1 PAKUSARI - Sandy, Perdana Arief; Sunardi, Sunardi; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2017)
Abstract. The purpose of this research was to determine whether the application of STAD cooperative learning model computer-assisted with Cabri 3D software affect on the student’s geometry ability. The population of this research is the students of grade X Pakusari Senior High School. The sample of this research was determined by cluster random sampling technique. Class X4 was selected as control class and class X5 as experiment class. The result of this research showed that the students geometry ability whom taught by STAD cooperative learning model computer-assisted with Cabri 3D software has increased than students whom taught by expository methods group based. It also appears that student activity at the experiment class is better than control class when group learning process held. There is a positive influence between the use of Cabri 3D software on the student’s geometry ability as a result of the application of STAD cooperative learning model computer-assisted with Cabri 3D software on matter of angle in three-dimensional space. It can be concluded that the application of STAD cooperative learning model computer-assisted with Cabri 3D software has an effect on geometry capability on matter of angle in three-dimensional space students of X grade Pakusari Senior High School. Keywords: STAD cooperative learning model, cabri 3D software, geometry ability.